A Particularly Dangerous Case of the Bubble Effect in Transformers That Appeared in a Large Mass of Pressboard Heated by Mineral Oil - Hubert Moranda; Hanna Moscicka-Grzesiak (Energies)
The topic concerns the so-far-unknown mechanism of the bubble effect (b.e.) in a large mass of moist cellulose heated with mineral oil. The well-known b.e. occurs in the Hot Spot area, i.e., in the place where the hot metal of the windings is in contact with the insulation paper. The authors first showed that cyclic heating of a windings model causes the drying of both the insulation paper and pressboard, but the paper dries faster. For this reason, the bubble effect inception temperature can be lower in the pressboard than in the paper. Next, the authors showed that the bubble effect in the pressboard is very intense and causes a sudden and very large increase in pressure in the tank. Moreover, if the tank seal is suddenly damaged because of this, the number and volume of bubbles will increase dramatically. Next, the influence of the mass of cellulose to the mass of oil ratio on the pressure increase dynamics was tested. This experiment showed that the greater the mass of cellulose to the mass of oil, the greater the increase in pressure in the test chamber. The authors also determined that the characteristics of the bubble effect initiation temperature in the pressboard samples, depending on their moisture content, ranged from 2.0 to 4.8%. The experiment showed that the b.e. in the pressboard proceeds in the same way as in paper insulation. The research results showed that, in addition to the well-known b.e. in the winding paper in the Hot Spot area, the b.e. can occur in a large mass of pressboard cellulose, which can be much more dangerous for the transformer.